Vitamin D as an adjunct to subcutaneous allergen immunotherapy in asthmatic children sensitized to house dust mite. Issue 2 (4th November 2013) - Baris, S.; Kiykim, A.; Ozen, A.; Tulunay, A.; Karakoc‐Aydiner, E.; Barlan, I. B.
Abstract Background We aimed to investigate the efficacy, safety, and T regulatory cell response of vitamin D as an adjunct to allergen‐specific immunotherapy (IT). Methods Fifty children with asthma and receiving pharmacotherapy were randomized into three groups as: subcutaneous IT (SCIT) along with vitamin D supplementation (650 U/day; n: 17), SCIT alone (n: 15), and pharmacotherapy alone (n: 18). All patients were evaluated at baseline, 6th and 12th months for scorings of symptoms and medication, skin prick testing, total IgE, specific IgE, and Der p 1‐specific IgG4. In addition, D. pteronyssinus‐induced CD4+CD25+FOXP3+T regulatory cell percentage, intracellular Foxp3 expression, and peripheral blood mononuclear cell IL‐10 and TGF‐β responses were assessed. Results In the SCIT + vitamin D and SCIT alone groups, total asthma symptom score (TASS), total symptom score (TSS), and total medication scores (TMS) were significantly lower than pharmacotherapy group at the end of 1 year. While the comparison of delta values (Δ 6th and Δ 12th month − baseline) of those scores revealed no significant differences between the two IT groups, TASS at the 6th month was lower in the SCIT + vitamin D group compared with others. There was a significant and positive trend in the levels of Der p 1‐specific IgG4 in both IT groups throughout the study period. Whereas the levels of Der p 1‐induced IL‐10 and TGF‐β were similar between IT groups, the mean fluorescence intensity of Foxp3 was highest in the SCIT + vitamin D group compared with others at the 12th month. The rate of discontinuation of inhaled corticosteroid (ICS) was 6/17 in SCIT + vitamin D, 3/15 in SCIT, and 0/18 in the pharmacotherapy group (P = 0.02). Conclusion Both SCIT groups fared better than pharmacotherapy alone at the end of 1 year. Although the clinical and immunologic outcomes were mostly similar between the two IT groups, some favorable outcomes of vitamin D warrant further investigation in more selected populations with varying doses as adjunct to IT.